Cytokine mass balance levels in donation after circulatory death donors using hemoadsorption: Case series report. Issue 7 (July 2022) - Baroni, Stefano; Marudi, Andrea; Rinaldi, Simone; Ghedini, Silvia; Magistri, Paolo; Piero Guerrini, Gian; Olivieri, Tiziana; Dallai, Chiara; Talamonti, Marta; Maccieri, Jessica; Benedetto, Fabrizio Di; Bertellini, Elisabetta
The use of hemadsorption has been purposed to reduce cytokine levels during the reperfusion phase during donation after circulatory death (DCD) programs. This paper aims to describe a cases series of the inflammatory cytokine levels before and after hemadsorption during normothermic reperfusion in DCD donors of liver and kidneys. In this observational pilot paper, we describe 8 DCD donors of liver or kidneys in our center from the year 2018 to 2019. All DCD donor subjects had similar age, were younger than 60 years, without evident critical conditions, no liver or kidney dysfunction known, and they presented with poor neurological outcomes instrumentally and clinically documented. We observed in our patients an interesting reduction of IL-10 and TNF-α levels during the normothermic reperfusion with hemadsorption. We transplanted all livers and kidneys from DCD donors without significant compliances.